MCDONALD'S APPLICATION ANALYSIS USING TECHNOLOGY ACCEPTANCE MODEL (TAM) - Saputra, Lucky Abdullah; Sekarwati, Kemal Ade (Asosiasi Dosen Muda Indonesia, 2024)
McDonald's application is an application developed and published by McDonald's Apps. This application aims to provide ordering services to consumers through online without having to come to the outlet. This study aims to explain and analyze user acceptance of McDonald's applications. In this study, the acceptance theory used is the modification and development of the Technology Acceptance Model theory which focuses on five factors, namely usability perception factors, ease perception, usage attitude, usage interest and actual use. The method in this study is quantitative with data analysis techniques using descriptive analysis techniques and using multiple linear regression analysis with the help of IBM SPSS Version 25 software. The sample taken amounted to 100 respondents with characteristics who used or who had used the McDonald's application at least once. The sampling technique uses the Non-probability Sampling method with the Purposive Sampling technique. The results obtained from the analysis using IBM SPSS are (1) usability perception positively affects usage attitude, (2) convenience perception positively affects usage attitude, (3) usability perception positively affects usage interest, (4) usage attitude positively affects usage interest, (5) usability perception positively affects actual use and (6) use interest positively affects actual use. In conclusion, all hypotheses that have been formulated are accepted. The residual data of the variable are independent of the normally distributed dependent variable and the regression model satisfies the normality assumption. Independent and dependent variables do not occur heteroscedasticity problems. Independent and dependent variables do not occur multicollinearity. Independent and dependent variables have no autocorrelation.